To assess the role of cataract extraction in glaucoma management by its intraocular pressure lowering effect - Muhammad Ifraheem Khan; Saba Ali Arif; Muhammad Tanweer Hassan Khan; Muhammad Adnan Khan; Muhammad Saleem (Journal of the Pakistan Medical Association, 2021)
Objective: To measure the mean change of intraocular pressure (IOP) in glaucoma patients with cataract after uncomplicated phacoemulsification surgery with intraocular lens (IOL) implanted in capsular bag. Methods: A total of 40 patients who had uncomplicated cataract extraction by phacoemulsification with IOL implant in the capsular bag in glaucomatous eyes of age 30-80 years were included. Patients with corneal pathologies or had corneal refractive procedure, history of ocular trauma, uveitis, retinal pathologies or other ocular comorbids were excluded. Visual acuity, IOP, slit lamp examination, fundoscopy, visual fields, details about topical medication and relevant history was recorded not more than 5 days before cataract extraction. IOP was recorded (first individually, then average of all) by Goldman’s applanation tonometer one day before surgery, 1 month and 3 months post op. Results: Age range in this study was from 30 to 80 years with mean age of 52.23 ± 9.44 years. Majority of the patients i.e. 28 (70.0%) were between 30 to 55 years of age. Out of these 40 patients, 19 (47.50%) were male and 21 (52.50%) were females with male to female ratio of 1:1.1. Mean pre-operative IOP was 20.42 ± 1.69 mmHg, after 1 month of surgery was 18.55 ± 0.90 mmHg and after 3 months was 17.03 ± 1.19 mmHg (p-value = 0.0001). Conclusion: This study concluded that there is significant change of intraocular pressure in glaucoma patients with cataract after uncomplicated phacoemulsification surgery with IOL implanted in capsular bag. Keywords: Glaucoma, phacoemulsification, intraocular pressure Continuous...